Dinamika Kalium Tanah dan Hasil Padi Sawah (Oryza sativa L.) akibat Pemberian NPK Majemuk dan Penggenangan pada Fluvaquentic Epiaquepts - Muhammad Imam Al Mu'min; Benny Joy; Anni Yuniarti (Soilrens, 2016)
This experiment aimed to find out the effect of application NPK compound and water regulation on soil potassium  and  yield  of  rice  (Oryza  sativa L.) on  Fluvaquentic  Epiaquepts.  This  experiment  was conducted  from  May to October 2015,  at  paddy field  of  Soil and  Water  Management,  Soil Science and Land Resources Department, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang. The experiment was arranged in Randomized Block Design consisted of ten treatments and three replications.The treatment consisted of : Control, Waterlogged 5 cm; 150 kg NPK ha-1, Waterlogged 5 cm; 300 kg NPK ha-1, Waterlogged 5 cm; 450 kg NPK ha-1, Waterlogged 5 cm; 600 kg NPK ha-1, Waterlogged 5 cm; 750 kg NPK ha-1, Waterlogged; local recommendation, Intermittent irrigation each 1 day until waterlogged; 450kg  NPK  ha-1, Intermittent  irrigation  each 3  days until waterlogged;  450 kg  NPK ha-1,  and  Intermittent irrigation each 5 days until waterlogged; 450 kg NPK ha-1. The results showed that there was effect of soil *potassium  and  yield  of  rice on  Fluvaquentic Epiaquepts.  The treatment  of  750  kg  NPK  ha-1 that waterlogged 5 cm give the highest result of Total Potassium, it was around 281,95 mg.kg-1, available of Potassium  was  around  0,45  cmol+.kg-1  and  the  highest  yield  was  7,02  kg.square-1  or  equal about  9,95 ton.ha-1. Keywords : Postassium, Inorganic Fertilizer Compound, Waterlogged, rice (Oryza sativa, L.)